ANALISA STANDAR WAKTU TERHADAP KINERJA KARYAWAN CV. BETON AGARA KUTACANE - Nasruddin, Nasruddin; Bu’ulolo, Deliman (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
Identify the problem in this research whether the leader sets the standard of Work Time, Employee Performance Assessment, and What form of employee standard work. This research is qualitative descriptive, data collecting method with field research by using method, observation and direct interview on research object to get description of research subject. From result of research, obtained data and information, that leader set standard work time 8 (Eight) hours per day , provided that the company does not work on religious holidays, especially Islamic holidays. The standard of assessment carried out for the workforce is the objective standard, in which the management of the company has determined the unit of outcome of the working time used. To produce the Culvert for the size of 80.60, and 40 Cm standard of production objectives set by the company as much as, 36 units employing 6 (people) Labor, while for the size of 30.20, and 15 Cm, ​​employed 4 people with labor standard 45 Goal Units. Furthermore For Production Pavin Blok has 3 (Three) production type, Rectangle, Six and Nuts. Standard destination 1.800 Units, with 4 Persons labor, and other production is the Hole of the Wind that is Utuk Pagas and Layang, the workforce can produce as many as 80 Units, labor used 2 Person.